Pengembangan Media Pembelajaran Board Game “Reproquest” untuk Mengenalkan Kesehatan Reproduksi Remaja di SMP Negeri 16 Kota Serang - Yerica Resty Anjaly, Caca; Meilla Dwi Nurmala; Alfiandy Warih Handoyo (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to develop an innovative learning medium in the form of a board game titled “ReproQuest: Adolescent Reproductive Health” to introduce and enhance students’ understanding of adolescent reproductive health at SMP Negeri 16 Kota Serang. The development process employed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) with eighth-grade students as research subjects selected through purposive sampling. The stages included analyzing student needs, designing an interactive game concept, and conducting feasibility and effectiveness tests. The feasibility assessment results showed an average score of 86.3% (categorized as highly feasible), consisting of 72.87% from linguists, 92.85% from media and material experts, and 87.5% from practitioners. A limited trial involving 10 students demonstrated improved understanding of reproductive health, with 70% of students achieving a moderate level and 30% reaching a high level of comprehension. These findings indicate that the “ReproQuest” board game is feasible, engaging, and effective as a learning medium and guidance tool to promote reproductive health education among adolescents. Moreover, it serves as an enjoyable and participatory learning alternative that fosters positive attitudes and awareness of reproductive health among junior high school students.